The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012 7th International Conference on System of Systems Engineering (SoSE) 2012
DOI: 10.1109/sysose.2012.6384140
|View full text |Cite
|
Sign up to set email alerts
|

The automatic identification system of maritime accident risk using rule-based reasoning

Abstract: To cite this version:Bilal Idiri, Aldo Napoli. The automatic identification system of maritime accident risk using rulebased reasoning. 7th International Conference on System Of Systems Engineering - IEEE SOSE 2012, Jul 2012, Genoa, Italy. pp.125-130, 2012, <10.1109/SYSoSE.2012

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…tuggingSpeed is a simple fluent expressing the intervals during which a vessel is said to be sailing at tugging speed (see Table 3). According to rule (8), two vessels are said to be engaged in tugging if one of them is a tug boat, neither of them is a pilot boat, and, for at least V Tug time-points, they are close to each other and sail at tugging speed.…”
Section: Tuggingmentioning
confidence: 99%
“…tuggingSpeed is a simple fluent expressing the intervals during which a vessel is said to be sailing at tugging speed (see Table 3). According to rule (8), two vessels are said to be engaged in tugging if one of them is a tug boat, neither of them is a pilot boat, and, for at least V Tug time-points, they are close to each other and sail at tugging speed.…”
Section: Tuggingmentioning
confidence: 99%
“…Their model incorporates the position, course, and speed of the ships in each route to identify the collision candidates. Son et al (2012) suggested a fuzzy algorithm to estimate collision risk among multiple ships in Korea using real-time AIS data, while Idiri and Napoli (2012) proposed a rule-based method applied to the movements of ships under changing sea conditions which would give an identification of the risks in real-time and potentially trigger an alarm to help prioritize interventions.…”
Section: Collision and Grounding Risk Assessmentmentioning
confidence: 99%
“…CEP component comprises a set of rules and knowledge to detect a predefined group of anomalies on the basis of the receiving event attribute which are the same in [31][32][33]. The rule base specifies how to infer complex events from the event stream.…”
Section: Lida-e Enginementioning
confidence: 99%